CLINICAL EVALUATION OF EFFICACY OF KUSTHADI CHURNA WITH UDUMBARADI TAILA IN THE MANAGEMENT OF KARNINI YONIVYAPAD W.S.R. TO CERVICAL EROSION - Ranju Kumari, Chaurasia; Jain, C.M.; Pushplatha, B.; Bharathi, K. (International Journal of Ayurveda and Pharma Research, 2016)
Karnini yonivyapad is one of the gynaecological disorders described in Ayurveda under the umbrella of the Yonivyapad. According to the signs and symptoms, it is more nearer to the benign lesion cervical erosion, which occurs due to the replacement of the stratified squamous epithelium of the portio-vaginalis by the columnar epithelium of endocervix. The treatment is designed to destruct the columnar epithelium by any method and to promote the re-epithelization of the squamous tissues. Keeping this point in view, the present clinical trial is taken up with the aim of clinical evaluation of efficacy of Kusthadi churna with Udumbaradi taila in the management of Karnini yonivyapad (cervical erosion). Kusthadi churna along with Yonipichu with Udumbaradi taila group-A, and group-B only Udumbaradi taila yonipichu, and results were assessed on the basis of the epithelization of erosion and improvement in the symptoms. The study reveals that the mixed therapy group showed better results than the group of single drug.